Analisis Keberlanjutan Usahatani Padi Organik di Kecamatan Kamang Magek dan Kecamatan Canduang Kabupaten Agam Sumatera Barat - Maulidia, Fatia Zahara; Yusri, Jumatri; Edwina, Susy (Universitas Galuh, 2025)
Kamang Magek and Canduang Districts contain organic rice farmers as a form of government success in voicing sustainable agricultural systems in West Sumatra. Organic rice farming in this location has problems with the decreasing number of organic rice farmers, limited organic land, and the absence of an organic market so the price of organic rice obtained by farmers is not by the market price of organic rice on the market. This study aims to determine the sustainability status of organic rice farming in Kamang Magek and Canduang Districts and to identify sensitive attributes of organic rice farming. This study uses a survey method with a sample taken by a census of 30 organic rice farmers, and data collection is carried out using a questionnaire. Data analysis was carried out using the multidimensional scaling (MDS) method and RAP-Organic software. The study results indicate that organic rice farming in Kamang Magek and Canduang sub-districts has a fairly sustainable status. The ecological dimension has a sustainable status with its sensitive attributes, namely plant health and biodiversity, soil nutrient/fertility levels, and the amount of organic fertilizer/pesticide used per unit of land. The social dimension has a fairly sustainable status with its sensitive attributes, namely the level of farmer education, access to resources and assistance, food independence, farmer knowledge and awareness of resource conservation, and fairness in income distribution. The economic dimension is a dimension that has a less sustainable status with its sensitive attributes, namely the price of organic rice, the availability of organic rice markets, the benefit-cost ratio, and the status of organic rice land ownership.